Evidence-Based Health Informatics - Promoting Safety and Efficiency through Scientific Methods and Ethical Policy - M. Rigby (ed.); E. Ammenwerth (ed.) (IOS Press, 2016)
"Health IT is a major field of investment in support of healthcare delivery, but patients and professionals tend to have systems imposed upon them by organizational policy or as a result of even higher policy decision. And, while many health IT systems are efficient and welcomed by their users, and are essential to modern healthcare, this is not the case for all. Unfortunately, some systems cause user frustration and result in inefficiency in use, and a few are known to have inconvenienced patients or even caused harm, including the occasional death. This book seeks to answer the need for better understanding of the importance of robust evidence to support health IT and to optimize investment in it; to give insight into health IT evidence and evaluation as its primary source; and to promote health informatics as an underpinning science demonstrating the same ethical rigour and proof of net benefit as is expected of other applied health technologies. The book is divided into three parts: the context and importance of evidence-based health informatics; methodological considerations of health IT evaluation as the source of evidence; and ensuring the relevance and application of evidence. A number of cross cutting themes emerge in each of these sections. This book seeks to inform the reader on the wide range of knowledge available, and the appropriateness of its use according to the circumstances. It is aimed at a wide readership and will be of interest to health policymakers, clinicians, health informaticians, the academic health informatics community, members of patient and policy organisations, and members of the vendor industry."
English
Keywords: health; health informatics; IT; healthcare; policy; policymakers